2012
DOI: 10.1029/2011wr011567
|View full text |Cite
|
Sign up to set email alerts
|

Plume spreading in groundwater by stretching and folding

Abstract: [1] This paper proposes a new approach to the hydraulics of in situ groundwater remediation. In situ remediation promotes reactions between an injected treatment solution and the contaminated groundwater, but without a hydraulic mechanism to promote spreading, the laminar flows characteristic of porous media will keep the two fluids in approximately the same relative configuration as they travel through the aquifer, limiting the opportunity for reactions to occur. To address this fundamental limitation, this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 41 publications
3
71
0
Order By: Relevance
“…The limiting role of mixing to the overall transformation rates of contaminants in the subsurface is increasingly recognized as well as the importance of mixing enhancement by natural flow and transport processes (e.g., Rolle et al, 2009;Werth et al, 2006) and engineered approaches (Kitanidis and McCarty, 2012;Mays and Neupauer, 2012;Trefry et al, 2012). Moreover, there is a clear need to distinguish between true mixing processes, depending on aqueous diffusion, and processes such as advective heterogeneities, which may lead to squeezing, stretching and meandering of a solute plume but do not directly contribute to physical mixing.…”
Section: Metrics Of Mixingmentioning
confidence: 99%
“…The limiting role of mixing to the overall transformation rates of contaminants in the subsurface is increasingly recognized as well as the importance of mixing enhancement by natural flow and transport processes (e.g., Rolle et al, 2009;Werth et al, 2006) and engineered approaches (Kitanidis and McCarty, 2012;Mays and Neupauer, 2012;Trefry et al, 2012). Moreover, there is a clear need to distinguish between true mixing processes, depending on aqueous diffusion, and processes such as advective heterogeneities, which may lead to squeezing, stretching and meandering of a solute plume but do not directly contribute to physical mixing.…”
Section: Metrics Of Mixingmentioning
confidence: 99%
“…The results showed that the effects of aquifer heterogeneity were insignificant under the forced recirculation scheme [ Gandhi et al ., ]. Enhanced mixing by stretching and folding can be induced with pulsed injection and extraction of clean water outside of a plume [ Mays and Neupauer , ]. This mixing promotes reaction between an injected treatment solution and the contaminant [ Piscopo et al ., ].…”
Section: The Dissolved Organic Contaminant Plumementioning
confidence: 99%
“…Sites where aquifer hydraulics vary less tend to have long, thin, and relatively uniform plumes; conversely, sites with highly varying hydraulic conditions tend to have wider plumes with more irregular contaminant distribution. Researchers in chaos theory describe this element of transport as plume stretching and folding (Bagtzoglou and Oates ; Mayes and Neupauer ; Ottino ; Piscopo et al ).…”
Section: Introductionmentioning
confidence: 99%